PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN KEMATIAN - Yana Efitasari Duha (LPPM Universitas Nias Raya, 2026)
Legal Protection is an effort to protect the government or authorities or a number of existing regulations. A victim of a criminal act is someone who suffers physical, mental suffering and/or economic loss caused by a criminal act. The criminal act of accident is an incident on the road that results in human casualties and/or property loss. One of the traffic crimes that has been examined and tried by the High Court is decision number 29/Pid.Sus/2021/Pt.Dps. In this sentence, the perpetrator was sentenced to 5 (five) months in prison for violating Article 310 paragraph (4) Number 22 of 2009. The type of research used by the author is normative research using the statutory and regulatory approach, case method, and analytical approach. Data collection was carried out using secondary data, which was obtained through library materials consisting of primary materials, secondary legal materials and theoretical legal materials. The data analysis used was descriptive qualitative analysis and conclusions were drawn using the deductive method. Based on the research findings and discussion, as in the sentence, the judge sentenced Article 310 paragraph (4) number 22 of 2009 with a sentence of 5 (five) months in prison, but in Article 310 paragraph (4) and as referred to in paragraph (3) a maximum prison sentence of 6 (six) years in prison and/or a fine of 12,000,000.00 (twelve million rupiah) but in the judge's sentence the perpetrator was only sentenced to 3 (three) months in prison. Based on this, the victim filed an appeal at the Denpasar High Court and the perpetrator was sentenced to 5 (five) months in prison. However, this second decision does not reflect the values ​​of justice for the victims or their heirs. So the panel of judges should pay attention to the decision against the perpetrator, because the decision can protect the rights of the victim/or their heirs and can provide justice for the victim/heirs.